Single Gaussian Chaotic Neuron: Numerical Study and Implementation in an Embedded System - Luis M. Torres-Treviño; Angel Rodríguez-Liñán; Luis González-Estrada; Gustavo González-Sanmiguel (Discrete Dynamics in Nature and Society)
Artificial Gaussian neurons are very common structures of artificial neural networks like radial basis function. These artificial neurons use a Gaussian activation function that includes two parameters called the center of mass (cm) and sensibility factor (λ). Changes on these parameters determine the behavior of the neuron. When the neuron has a feedback output, complex chaotic behavior is displayed. This paper presents a study and implementation of this particular neuron. Stability of fixed points, bifurcation diagrams, and Lyapunov exponents help to determine the dynamical nature of the neuron, and its implementation on embedded system illustrates preliminary results toward embedded chaos computation.